SME Innovation management:A study of Vietnam’s Healthcare industry - NGUYEN, THI THU THUY (2018)
Innovation is a broad concept. Therefore, to study innovation pathway in Vietnam, this research only focuses on one aspect of innovation: product development. Next, the author chose a small industry that is medical equipment business to analysis. From SME point of view (the majority of enterprises in the Vietnam market), innovation pathway in Vietnam was discovered.